ANALYSIS OF GOOD CORPORATE GOVERNANCE, LEVERAGE, AND COMPANY SIZE AGAINST PROFIT MANAGEMENT - Sukarni Crystianty Suhaili; Vargo Christian L. Tobing (Jurnal Ekonomi, 2023)
The study aims  to examine the   effect of Good Corporate Governance, Leverage and company size on  profit management in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017 – 2021.  This research is a quantitative study with a data collection method  using purposive sampling to obtain results that match  the  criteria.  Based on the predetermined criteria, a total sample  of  23 companies with a  research period of 5 years was obtained,  so that 115 samples were obtained.  However, there were 38 outlier data in this study, bringing the sample tested to 77 samples. This study used SPSS 25 in analyzing the data.  The results of  this study show that  managerial ownership  affects profit management  , while institutional ownership and an independent board of commissioners have no effect on profit management. These three variables are variants used to test Good Corporate Governance.  Furthermore, the variable leverage has a positive and significant effect on profit management and the  size of the  company has a negative and significant effect   on profit  management.  Also obtained,  managerial ownership,  institutional ownership, independent  board of commissioners, leverage and size  The company    exerts an influence on  profit management.